Normal translation of human adenovirus mRNA in cell-free lysates prepared from abortively as well as productively infected monkey cells. - Quinlan, M P (1982)
A variety of mRNAs, including adenovirus-specified mRNAs isolated from infected human cells, were translated with similar efficiencies in S10 cell-free lysates prepared from productively and abortively infected monkey cells. These results may suggest that reduced synthesis of the late viral proteins in abortively infected monkey cells is not due to a defect in the protein-synthesizing apparatus of the cell.